PENGARUH SUHU DAN LAMA PEMANASAN TERHADAP KESTABILAN PEWARNA ALAMI DARI PULP BUAH LONTAR - Nana, Yusta Un; Picauly, Intje; Mahayasa, I Nyoman W. (Pergizi Pangan DPD NTT, 2011)
This purpose of research to know the influence of temperature and duration of heater about the stability of natural dye from palmyra palm. Research method is the experiment to design the stake diserded the factual complement with 32 treatment ad 2 frequences by the duration variable of temperature start from 300C - 1000C temperature and duration variable heater start at 15 – 60 minutes. The stability colour to measure by using spectrophotometer method. The result statistic experiment about intesition pulp of palmyra palm the influence of temperature heater to show the different obvious (P < 0,05). For the treatment at 300C not different obvious at 1000C temperature yet obvious (P < 0,05) more small than treatment at 400C - 900C. The treatment 400C not different obvious at 500C - 1000C temperature, yet obvious (P < 0,05) more small than treatment at 300C.